Enlivening thinking and speech in search of spiritual identity: the role of 'speech formation' in Steiner's Waldorf education. Issue 1 (2nd January 2019) - Okumoto, Yoko
ABSTRACT: The purpose of this paper is to clarify Steiner's understanding of thinking and the way it influences the use of language in the classroom of 6–18 years old, and through that, to discuss how it eventually serves to capture one's spiritual identity. First, the paper introduces Steiner's notion of thinking, and then offers a general picture of what 'speech formation' is, and how it is actually used in a classroom. Secondly, the paper reviews Steiner's view on child development and examines his understanding of embodied thinking in accordance with will, feeling and 'I' consciousness. Finally, it considers the role of 'speech formation' in relation to the development of thinking and speech, and to the genius of language which comes to work in the 'space' created through dialogue. (129 words)